Structural, ferroelectric and photocatalytic performance of Ba1-xCaxTiO3 ceramics. (25th January 2020) - Suresh, P.; Mathiyalagan, P.; Srikanth, K. S.
Abstract: Ba1-x Cax TiO3 (Ca added BaTiO3 ; x = 0–0.3) ceramics is used as a target catalyst to probe the influence of ferro-electricity on the de-colorization of a typical dye molecule Methyl orange under visible light irradiation. The results indicated that there is a two fold increase in the de-colorization rate using Ba0.7 Ca0.3 TiO3 in around 180 min. This is ascribed to the ferro-electricity of the tetragonal phase. To probe the ferro-electricity in the catalyst, the P-E hysteresis loops show high polarization of 17.50 µC/cm 2 in x = 0.3 compared to 10 µC/cm 2 for x = 0 at 303 K. The high value of polarization in Ca added BaTiO3 enhances ferro-electricity and ensures a tightly bound layer of dye molecule and also acts to separate the photo-excited carriers due to the internal space charge layer. Both these features act to enhance the catalytic performance. Further, we studied the temperature dependence of dielectric study and it was found that dielectric constant increased and undergoes a maximum corresponding to a phase transition (330 K for x = 0.3) and thereafter decreased. The Ca substitution diffused the phase transition of BaTiO3 and resulted in shift of transition temperature towards room temperature with increase in content of Ca which is useful for many dielectric applications.